Zeitschrift für Assyriologie und Vorderasiatische Archäologie (De Gruyter, 1886)
The journal publishes papers and reviews from the field of Ancient Eastern Philology, and religious, legal, economic and social history, together with Middle Eastern archaeology and art history. The main geographical areas covered are Mesopotamia, Northern Syria, Anatolia, Ancient Armenia and Elam.